Inventário turístico rural em unidades ambientais estudo de caso: bacia hidrográfica das nascentes do rio Ibicuí-Mirim até a barragem Saturnino de Brito - Paim, Ailton Fernandes (2009)
Tourism has among its characteristics the dependence on the free time of people who travel, an unstable demand for intangible and diversified products, different public according to the season of year and static environment without the possibility of stocking its production. Besides the public, receptive, food, transportation, recreational and entertainment services, the touristic product is very important. It can be highlighted as a sum of: attraction + infra-structure + equipments + services + activities. The work developed in the watersheds of Ibicuí-Mirim River creates a new methodology of touristic inventory, joining researches in laboratories and field trips. By means of this model it aimed to identify the relevant items and the real conditions of the rural tourism in this region. The rural touristic inventory in environment units has a minimum number of items for the study progression. In case it is possible to research in this region we will be able to classify it into four classes of setting up the rural tourism. The pollution, the noise and the busy life of nowadays make people look for more preserved places and run away to natural environments near cities. The area studied deserves a greater attention for projects once the hydro watershed of Ibicuí-Mirim river is responsible for the water supply of Santa Maria, RS state and its quality depends on the actions which are being taken in this area.